Gambaran Kepuasan Hidup pada Dewasa Awal di Kota Kupang - Christian Eprilio Kolobani (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
Life satisfaction is an important indicator of subjective well-being, particularly during early adulthood, a developmental stage characterized by various personal and social challenges. This study aimed to describe the level of life satisfaction among early adults in Kupang City, Indonesia. A quantitative approach with a descriptive design was employed. The study involved 384 respondents aged 18–25 years selected through proportionate stratified random sampling. Data were collected using the Satisfaction With Life Scale (SWLS) developed by Diener et al. and analyzed using descriptive statistical techniques. The findings revealed that most respondents were categorized as having a moderate level of life satisfaction (59.9%), followed by low (27.9%) and high (12.2%) levels. These results indicate that early adults in Kupang generally perceive their lives positively, although they have not yet reached an optimal level of life satisfaction. Social and economic factors, including employment opportunities, income, and environmental conditions, are assumed to contribute to their life evaluations. The study provides empirical evidence regarding life satisfaction among early adults and may serve as a reference for developing policies and programs aimed at improving youth psychological well-being.